Zerumbone-loaded nanostructured lipid carrier induces G2/M cell cycle arrest and apoptosis via mitochondrial pathway in a human lymphoblastic leukemia cell line - Rahman, Heshu Sulaiman; Abdullah, Rasedee; Abdul, Ahmad Bustamam; Allaudin, Zeenathul Nazariah; Othman, Hemn Hassan; Yeap, Swee Keong; How, Chee Wun; Wan Abd Ghani, Wan Nor Hafiza (Dove Medical Press, 2014)
This investigation evaluated the antileukemia properties of a zerumbone (ZER)-loaded nanostructured lipid carrier (NLC) prepared by hot high-pressure homogenization techniques in an acute human lymphoblastic leukemia (Jurkat) cell line in vitro. The apoptogenic effect of the ZER-NLC on Jurkat cells was determined by fluorescent and electron microscopy, Annexin V-fluorescein isothiocyanate, Tdt-mediated dUTP nick-end labeling assay, cell cycle analysis, and caspase activity. An MTT (3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide) assay showed that ZER-NLC did not have adverse effects on normal human peripheral blood mononuclear cells. ZER-NLC arrested the Jurkat cells at G2/M phase with inactivation of cyclin B1 protein. The study also showed that the antiproliferative effect of ZER-NLC on Jurkat cells is through the intrinsic apoptotic pathway via activation of caspase-3 and caspase-9, release of cytochrome c from the mitochondria into the cytosol, and subsequent cleavage of poly (adenosine diphosphate-ribose) polymerase (PARP). These findings show that the ZER-NLC is a potentially useful treatment for acute lymphoblastic leukemia in humans.